Mnenje osnovnošolskih učiteljev o usposobljenosti za sodelovanje s starši - Šrot, Kristina; Rizman Herga, Nataša (Revija za elementarno izobraževanje, 2013)
Primary School Teachers’ Perception of Their Qualification for Cooperating with Parents. The article presents a survey on teachers’ qualification for collaborating with parents of primary school children aged between 6 and 12. We investigated the most common difficulties that teachers face in communicating with parents and the way they tackle them. We differentiated the responses obtained according to the teachers’ years of service and the school environment they teach in. The teachers claimed that during their undergraduate studies, they had not received satisfactory training on how to communicate with parents. They believe they are not professionally qualified and they lack a wide array of competences which would facilitate their cooperation with parents. Some of the teachers’ observations are as follows: parents are generally willing to constructively exchange opinions about their children; some of them tend to overestimate their children’s abilities or are unequipped with skills on how to handle their child. One third of teacher respondents noted that they had experienced elements of aggressive behaviour in communicating with some parents. This is why we have introduced some guidelines which might help improve certain situations. In a learning society, teachers’ competences have been changing, becoming more complex and requiring teacher’s permanent professional advancement and adoption of modern educational trends. At the same time, we realise that communication is a twoway interdependent process. Along with the competences of a teacher, we must therefore also consider the competences of parents and their contribution to quality cooperation and effective communication.
Keywords: education; teachers’ competences; cooperation with parents; relations; obstacles of communication